Lower limb injuries in children in sports - Bruns, W.; Maffulli, N. (Clinics in Sports Medicine, 2000)
This article presents an overview of sports-related injuries of the lower limb in children, with emphasis on the management. The special injury-related conditions of childhood, epidemiology, and the particular pattern of injuries are discussed. The increased participation of children in sports will continue. Permanent damage is a risk, and, as such, prevention should be the most important management in this age group. For example, stretching exercises should be performed with "warm" muscles. Excessive weight training has an unacceptable risk of injury. In endurance sports, the "10 percent rule," which consists of increasing activity by 10% each week, probably could be applied to prevent overuse injuries. A multifactorial approach may be helpful. The rationale for high performance, competitive sports for children is doubtful. The optimal levels of safe training will remain changeable and not predictable. It should be the responsibility of parents, coaches, and healthcare professionals to try and minimize the potential for injury and disability, and allow children to enjoy the benefits of sports.